2020
DOI: 10.1200/jco.2020.38.15_suppl.6066
|View full text |Cite
|
Sign up to set email alerts
|

ctDNA from ascites as an alternative to tumor sampling for HRD (homologous recombination deficiency) testing in ovarian cancer (OC).

Abstract: 6066 Background: Knowledge regarding HRD status is becoming crucial to guide maintenance strategies for patients with newly diagnosed OC. Unfortunately, for patients (pts) treated with neoadjuvant chemotherapy (NACT), HRD testing on small biopsies from diagnostic laparoscopies (Dx Lap) or interval debulking has a high failure rate. At relapse, biopsies may not be feasible. Aim: Evaluate the feasibility and usefulness of HRD testing on cfDNA from ascites Methods: Pts enrolled in a prospective biological study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In one study, circulating tumour DNA was identified in plasma from 29/33 (87%) blood samples, further analysis of ctDNA from ascites in 17 of these patients revealed that 10 had a high GIS (HRd), and seven a low GIS (HRp). 73 Genetic counselling is an essential element of patient care and should be available to any patients who have a family history of breast and/or ovarian cancer, hereditary germline mutations associated with increased cancer risk, or an abnormal tumour test (such as sBRCAm), as well as for those who request specific information. This approach is consistent with recent clinical practice guidelines for BRCA1/2 genetic testing, in which identifying individuals who may benefit from genetic counselling and riskreducing strategies is listed as the first aim of BRCA testing.…”
Section: Genetic Testing In the Clinicmentioning
confidence: 99%
“…In one study, circulating tumour DNA was identified in plasma from 29/33 (87%) blood samples, further analysis of ctDNA from ascites in 17 of these patients revealed that 10 had a high GIS (HRd), and seven a low GIS (HRp). 73 Genetic counselling is an essential element of patient care and should be available to any patients who have a family history of breast and/or ovarian cancer, hereditary germline mutations associated with increased cancer risk, or an abnormal tumour test (such as sBRCAm), as well as for those who request specific information. This approach is consistent with recent clinical practice guidelines for BRCA1/2 genetic testing, in which identifying individuals who may benefit from genetic counselling and riskreducing strategies is listed as the first aim of BRCA testing.…”
Section: Genetic Testing In the Clinicmentioning
confidence: 99%